Penerapan Metode Diskusi Hubungannya Dengan Berpikir Kritis Siswa Kelas XII IPA Madrasah Aliyah Miftahul Huda Subang - Muhamad Januaripin (Departement of Mathematics Education, 2023)
This research is motivated by phenomena that occur in the area where the application of discussion methods has been well done, but the critical thinking of students is still relatively low. This research was conducted at Madrasah Aliyah Miftahul Huda Subang using a correlational descriptive quantitative method, which is a method that serves to describe or describe the object under study through data or samples that have been collected to determine the relationship between variables. Research data was collected through a survey of 26 students from Science Class XII Madrasah Aliyah Miftahul Huda Subang. The data analysis technique used in this research was based on the IBM SPSS 21 statistical processing application. Based on the results of research data analysis, it was concluded that there was a significant (meaningful) relationship between the application of discussion methods and students' critical thinking with a strong and positive level of relationship, getting a value of 0.741 in the interval 0.51-0.75 so that the relationship between the two variables was unidirectional which could mean that the better the application of the discussion method, the better the level of critical thinking of students.